Pattern recognition and image analysis : 9th Iberian Conference, IbPRIA 2019, Madrid, Spain, July 1-4, 2019, Proceedings.: 9th Iberian Conference, IbPRIA 2019, Madrid, Spain, July 1-4, 2019, Proceedings. Part II (2019) - Unknown
No abstract available